Comparative Study for Organic and Inorganic Draw Solutions in Forward Osmosis - Al-Alalawy, Ahmed Faiq; Abbas, Talib Rashid; Mohammed, Hadeer Kadhim (Al-Khwarizmi Engineering Journal, 2017)
The present work aims to study forward osmosis process using different kinds of draw solutions and membranes. Three types of draw solutions (sodium chloride, sodium formate, and sodium acetate) were used in forward osmosis process to evaluate their effectiveness with respect to water flux and reverse salt flux. Experiments conducted in a laboratory-scale forward osmosis (FO) unit in cross flow flat sheet membrane cell. Three types of membranes (Thin film composite (TFC), Cellulose acetate (CA), and Cellulose triacetate (CTA)) were used to determine the water flux under osmotic pressure as a driving force. The effect of temperature, draw solution concentration, feed and draw solution flow rate, and membrane types, were studied with respect to water flux. The results showed an increase in water flux with increasing feed temperature and draw solution concentrations In addition, the flux increased with increasing feed flow rate while the flux was inversely proportional with the draw solution flow rate. The results showed that reverse osmosis membranes (TFC and CA) are not suitable for using in FO process due to the relatively obtained low water flux when compared with the flux obtained by forward osmosis membrane (CTA). NaCl draw solution gave higher water flux than other draw solutions and at the same time, revealed higher reverse salt flux.